Imaging of kidney cysts and cystic kidney diseases in children: an international working group consensus statement - Gimpel, Charlotte; Schaefer, Franz (Radiology, 2019)
Kidney cysts can manifest as focal disease (simple and complex kidney cysts),affect a whole kidney (eg, multicystic dysplastic kidney or cystic dysplasia), or manifest as bilateral cystic disease (eg, autosomal recessive polycystic kidney disease [ARPKD] or autosomal dominant polycystic kidney disease [ADPKD]). In children, as opposed to adults, a larger proportion of kidney cysts are due to genetic diseases (eg, HNF1B nephropathy, various ciliopathies, and tuberous sclerosis complex), and fewer patients have simple cysts or acquired cystic kidney disease. The purpose of this consensus statement is to provide clinical guidance on standardization of imaging tests to evaluate kidney cysts in children. A committee of international experts in pediatric nephrology, pediatric radiology, pediatric US, and adult nephrology prepared systematic literature reviews and formulated recommendations at a consensus meeting.The final statement was endorsed by the European Society of Pediatric Radiology, the European Federation of Societies for Ultrasound in Medicine and Biology, the European Society of Pediatric Nephrology, and reviewed by the European Reference Network for Rare Kidney Diseases. Main recommendations are as aollows: US is the method of choice when assessing pediatric kidney cysts, with selected indications for MRI and contrast-enhanced US. CT should be avoided whenever possible because of ionizing radiation. Renal US yields essential diagnostic information in many cases. In patients with ARPKD or other ciliopathies, abdominal US is needed for diagnosis and screening of portal hypertension. US is usually sufficient for follow-up kidney imaging, but MRI can be valuable for clinical trials in patients with ADPKD or in older children with tuberous sclerosis complex to evaluate both kidney cysts and angiomyolipomas.© RSNA, 2018Online supplemental material is available for this article.